ß-Aminobutyric Acid-Induced Protection of Arabidopsis against the Necrotrophic Fungus Botrytis cinerea - Zimmerli, Laurent; Métraux, Jean-Pierre; Mauch-Mani, Brigitte (My University, 2001)
The non-protein amino acid ß-aminobutyric acid (BABA) protects numerous plants against various pathogens. Protection of Arabidopsis plants against virulent pathogens involves the potentiation of pathogen-specific defense responses. To extend the analysis of the mode of action of BABA to necrotrophs we evaluated the effect of this chemical on Arabidopsis plants infected with the gray mold fungus Botrytis cinerea. BABA-treated Arabidopsis were found to be less sensitive to two different strains of this pathogen. BABA protected mutants defective in the jasmonate and ethylene pathways, but was inactive in plants impaired in the systemic acquired resistance transduction pathway. Treatments with benzo-(1,2,3)-thiadiazole-7-carbothioic acid S-methyl ester, a functional analog of salicylic acid (SA), also markedly reduced the level of infection. Moreover, BABA potentiated mRNA accumulation of the SA-associated PR-1, but not the jasmonate/ethylene-dependent PDF1.2 gene. Thus, besides jasmonate/ethylene-dependent defense responses, SA-dependent signaling also contributes to restrict B. cinerea infection in Arabidopsis. Our results also suggest that SA-dependent signaling is down-regulated after infection by B. cinerea. The observed up-regulation of the PDF1.2 gene in mutants defective in the SA-dependent signaling pathway points to a cross-talk between SA- and jasmonate/ethylene-dependent signaling pathways during pathogen ingress.